Analisis Pekan Liga Literasi Dan Numerasi Pada Kurikulum Merdeka Siswa Kelas V SDN 18 Tubung - Ermawati Ermawati; Ahmad Khoiri (Scholarly Journal of Elementary School, 2026)
Abstract The Literacy and Numeracy League Week is an implementation of the Merdeka Curriculum aimed at improving students’ literacy and numeracy skills while fostering a fun and contextual learning culture. This study aims to describe the activity design, implementation, challenges, and efforts undertaken in the Literacy and Numeracy League Week at SDN 18 Tubung. This research employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The research subjects were fifth-grade students of SDN 18 Tubung. The results indicate that the design and implementation of the Literacy and Numeracy League Week generally ran well; however, improvements are still needed in the planning stage. The main challenges encountered were limited time and the shortage of committee members, which were addressed by involving students’ parents. Based on these findings, the Literacy and Numeracy League Week can serve as an alternative learning strategy for teachers and prospective teachers. Keywords: literacy, numeracy, league week.